1993
DOI: 10.1007/bf01883709
|View full text |Cite
|
Sign up to set email alerts
|

PI * S iiyama , a deficiency gene of alpha1-antitrypsin: Evidence for the occurrence in western Japan

Abstract: Summary An alphaa-antitrypsin deficiency associated with pulmonary emphysema was investigated in a 32-year-old Japanese male. Polymerase chain reaction (PCR)-amplified fragments and dot blot hybridization with allele-specific oligonucleotide probes revealed that the patient was homozygous for a C to T transition at codon 53, resulting in the substitution of Phe 53 for Ser 5~ (PI*Siiyama). Crossedimmunoelectrophoresis after isoelectric focusing and agarose gel electrophoresis showed atypical banding patterns. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…In contrast to this prevalence of acAT deficiency in Caucasians, only 12 cases of ai-AT deficiency have been reported in Japan (14-25; and K. Konishi, Iwate Medical University, School of Medicine, personal communication), including five cases for which the genetic defects have been elucidated, comprising one case of Mnichinan (19), two unrelated cases of Siiyama (21,22,25), a heterozygote of Mmalton (23), and a case of 14q -syndrome (18).…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…In contrast to this prevalence of acAT deficiency in Caucasians, only 12 cases of ai-AT deficiency have been reported in Japan (14-25; and K. Konishi, Iwate Medical University, School of Medicine, personal communication), including five cases for which the genetic defects have been elucidated, comprising one case of Mnichinan (19), two unrelated cases of Siiyama (21,22,25), a heterozygote of Mmalton (23), and a case of 14q -syndrome (18).…”
mentioning
confidence: 87%
“…In the present study, it was found that five unrelated families with (I.-AT deficiency, including eight deficient individuals, shared the same genetic defects in the (I.-AT gene, resulting in every case in the (I.-AT Siiyarna gene. Moreover, another, unrelated family carrying the Siiyarna gene was detected by another group(25). These results indicate that the (I.-AT deficient variant Siiyarna is highly prevalent in Japan, being detected in seven (70070) of 10families with (I.-AT deficiency who were examined at the level of the (I.-AT gene.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Interestingly, this disease is quite rare in Japan, and we believe this report presents the sixteenth trait found in the Japanese population. All of the reported cases in Japan are listed in Table 1 (4,(7)(8)(9)(10)(11)(12)(13)(14)(15). While ZZ homozygote is the most common cause of AAT deficiency in Caucasians, Siiyama variant was the primary cause among the Japanese cases of AAT deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although this deficiency is among the most commonhereditary disorders in Caucasians (1), it is very rare among Orientals; gene frequencies of deficient alleles are estimated to be extremely low. Considering all Asian countries, only 13 Japanese families and one Chinese family with alAT deficiency have been reported (3)(4)(5)(6)(7)(8)(9). Consanguineousmarriage was noted in most of these families.…”
Section: Introductionmentioning
confidence: 99%